Utilization of Complementary and Alternative Medicine Among Adults in Riyadh: Pharmaceutical Science-Medicine - A Alfadeel, Mona; H. Alanazi, Haya; M. Alshabi, Malak; A. Zubaidi, Ghuzlan; K. Alshariri, Kholod; S. Alharegi, Dalal; T. Alanzi, Mashael; A. Alotaibi, Ghada; M. Abdi, Alaa; S. Abudeyah, Razan; S. Alfawaz, Renad (International Journal of Life Science and Pharma Research, 2022)
The interest in the use of complementary and alternative medicine (CAM) has been well documented. Knowledge, Attitude, and Practices (KAP) studies in CAM are critical for paving the way for intervention efforts to raise awareness. The aim was to measure the knowledge and attitudes of adults and to identify the factors associated with the use and practice of Complementary and Alternative Medicine (CAM) in Riyadh, Saudi Arabia. An observational cross-sectional, community-based, and multi-center study was conducted. After receiving consent, data were collected using a Google form-based online questionnaire. Most of the participants (82.5%) preferred to use CAM in combination with conventional medicine. The most common health problems were menstrual pain (49.5%) and abdominal pain (24.5%). The commonly used CAM remedies in this study were honey (65%) and Zamzam (Believed to be blessed holy water in the Islamic faith) (59.6%). The common causes given by the participants for preferring CAM remedies were because they were natural products (34%) and also avoiding the side effects of drugs (33.5%). Participants younger than 18 were the most supportive age group. Honey was the most chosen modality, contrary to the findings of the Qassim study. It was found that the common cold was the commonest reason for CAM use in the study’s population, whereas in the Bahrain study diabetes mellitus was the reason. In conclusion, awareness about CAM was remarkably high among the participants of this study. A high proportion of respondents prefer to use CAM along with traditional medicines. The high proportion use of CAM encountered in this study was remarkable for the health education that addresses both advantages and drawbacks of CAM. Proper scientific research into safety and effectiveness is needed.